2023
DOI: 10.1021/acs.jafc.3c02471
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Umami Peptides Specific to the T1R1/T1R3 Receptor via Phage Display

Mingyang Li,
Xiaoyu Zhang,
Yiwen Zhu
et al.

Abstract: Umami peptides are small molecular weight oligopeptides that play a role in umami taste attributes. However, the identification of umami peptides is easily limited by environmental conditions, and the abundant source and high chromatographic separation efficiency remain difficult. Herein, we report a robust strategy based on a phage random linear heptapeptide library that targets the T1R1-Venus flytrap domain (T1R1-VFT). Two candidate peptides (MTLERPW and MNLHLSF) were readily identified with high affinity fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…In addition, food scientists have shown considerable interest in implementing this technique in food allergy diagnosis, biotoxin, and foodborne pathogenic bacterial detection. More recently, Li et al screened a phage random linear 7-mer peptide library to identify two candidate peptides (MTLERPW and MNLHLSF) that bind to the umami receptor’s venus flytrap domain (T1R1-VFT) with high affinity ( K d = 790 and 630 nM, respectively). They further validated that these two peptides display an umami taste and significantly enhance the umami intensity in monosodium glutamate solution, suggesting that phage display is a promising tool for discovering taste peptides …”
Section: Strategies To Develop Rice Bran Lipase Inhibitorsmentioning
confidence: 82%
“…In addition, food scientists have shown considerable interest in implementing this technique in food allergy diagnosis, biotoxin, and foodborne pathogenic bacterial detection. More recently, Li et al screened a phage random linear 7-mer peptide library to identify two candidate peptides (MTLERPW and MNLHLSF) that bind to the umami receptor’s venus flytrap domain (T1R1-VFT) with high affinity ( K d = 790 and 630 nM, respectively). They further validated that these two peptides display an umami taste and significantly enhance the umami intensity in monosodium glutamate solution, suggesting that phage display is a promising tool for discovering taste peptides …”
Section: Strategies To Develop Rice Bran Lipase Inhibitorsmentioning
confidence: 82%
“…Previous studies indicated that umami peptides not only provide but also contribute to the umami taste, thus reducing the intake of MSG. , The umami-enhancing effects of six peptides were further investigated by adding them to the 0.35% MSG solution separately. As shown in Figure b, the six umami peptides showed different extents of synergistic effects with 0.35% MSG solutions, which may be related to the synergistic effect between the umami peptides and MSG .…”
Section: Resultsmentioning
confidence: 99%
“…Each sample was swirled for 15 s before spitting out. To avoid the influence of residual sample and taste fatigue, panelists were instructed to rinse their mouth twice with at least 50 mm of ultrapure water for 15 s before each test . The sensory threshold of team members is considered to be reached when they cannot distinguish blanks and samples.…”
Section: Methodsmentioning
confidence: 99%